An experimental examination of worry and relaxation on cardiovascular, endocrine, and inflammatory processes - Renna, Megan E. (Psychoneuroendocrinology, 2020)
BACKGROUND: Worry increases risk for long-term health issues by prolonging the physiological stress response. In contrast, relaxation may ameliorate the psychological and physiological burden resulting from worry. This study examined the impact of experimentally induced worry and relaxation on cortisol, heart rate variability (HRV), and inflammation. METHOD: Participants (N = 75) completed both a worry and relaxation induction (presented in a fixed order) while HRV was collected continuously. Three blood samples were taken (at baseline, after the worry induction, and after the relaxation induction) to measure IL-6, IFN-γ, TNF-α and serum cortisol. RESULTS: There were significant changes in IL-6 (p < 0.001), IFN-γ (p < 0.001), HRV (p < .001), and cortisol (p < .001) but not in TNF-α (p = 0.19) across conditions. IFN-γ and HRV increased significantly from baseline to worry and then decreased following relaxation. IL-6 changed significantly between worry and relaxation and continued to increase following relaxation. Cortisol decreased significantly across conditions. Several patterns of covariance between inflammation and HRV and/or cortisol also emerged. CONCLUSIONS: These findings offer novel insight into how worry influences the immune system and emphasize the utility of a multi-methods approach to understanding the impact of worry on physical health.